2011
DOI: 10.1089/omi.2010.0093
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 −174G/C Polymorphism and IL-6 Serum Levels in Patients with Liver Cirrhosis and Hepatocellular Carcinoma

Abstract: Recently, a link between high levels of circulating IL-6 and hepatocellular carcinoma (HCC) has been proposed. In addition, single nucleotide polymorphisms (SNPs) in the promoter region of the IL-6 gene have been reported to be related to several inflammatory-related conditions, including cancer. The purpose of this article is: (1) to evaluate the frequencies of SNPs in the IL-6 promoter region at position -174 and IL-6 serum levels in a group of patients with HCC and underlying liver cirrhosis (LC), and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 20 publications
1
31
0
4
Order By: Relevance
“…Furthermore, Coskun et al showed that in breast cancer patients, higher serum levels of IL-6 could be used to distinguish primary or metastatic liver tumors from benign HCC lesions (152). Studies focusing on the association between IL-6 polymorphisms and HCC risk are still controversial, further studies are warrented to clarify these differing findings (153)(154)(155).…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%
“…Furthermore, Coskun et al showed that in breast cancer patients, higher serum levels of IL-6 could be used to distinguish primary or metastatic liver tumors from benign HCC lesions (152). Studies focusing on the association between IL-6 polymorphisms and HCC risk are still controversial, further studies are warrented to clarify these differing findings (153)(154)(155).…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%
“…IL-6 is a multifunctional cytokine that serves pro-and anti-inflammatory functions. The level of IL-6 is higher in HCC patients than in healthy individuals (Giannitrapani et al, 2011). Numerous cytokines participate in the construction of a highly complex and coordinated network in which they modulate their own synthesis and that of other cytokines (Balkwill et al, 1989;Elias et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study conducted in Turkey (Ataseven et al, 2006) measured the IL-6 serum level among 70 subjects in total, and found that the serum level was correlated with the disease advancement. The latest epidemiological approach performed in Italy observed similar trend between IL-6 serum level and HCC, furthermore, the G carriers of -174G/C polymorphism had higher IL-6 serum level in HCC patients than that of subjects with LC (Giannitrapani et al, 2011). Polymorphisms in TNF-alpha may change the regulation of immune cells and malfunction of itself.…”
Section: Genetic Variationmentioning
confidence: 84%